La fabrication du beurre en Ethiopie: techniques traditionnelles et perpectives d'ameliorations - O'Mahony, F.; Bekele, E. (1985)
Summarises the results of a study on the traditional methods of butter making-conducted to determine the efficiency of the process and the quality of butter produced. Reports on initial experiments carried out to devise improved methods of butter making.